2018
DOI: 10.1016/j.ijthermalsci.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity and convective heat transfer downstream of a vortex generator

Abstract: Vorticity generation has been identified, since the 80's, as an efficient means for enhancing heat transfer; the mean radial velocity component due to the induced flow pattern contributes to the heat removal. In the present work, momentum and heat transfer are studied in a test section designed to mimic the industrial HEV (High-Efficiency Vorticity) mixer. It consists of a basic configuration with a unique vorticity generator inserted on the bottom wall of a heated straight channel. The aim of this work is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, compared with PIV and DNS, the current simulation does not generate a valley at the peak and shows a dropping‐rising velocity fluctuation at x/H = 0. The discrepancy in these results is mainly caused by lack of tab thickness in DNS and/or PIV inaccuracy in the low velocity region 30 …”
Section: Grid Independency and Validationmentioning
confidence: 94%
See 4 more Smart Citations
“…However, compared with PIV and DNS, the current simulation does not generate a valley at the peak and shows a dropping‐rising velocity fluctuation at x/H = 0. The discrepancy in these results is mainly caused by lack of tab thickness in DNS and/or PIV inaccuracy in the low velocity region 30 …”
Section: Grid Independency and Validationmentioning
confidence: 94%
“…To verify the prediction, the simulation for validation is performed under the same conditions of the previous PIV, 7 DNS, 40 and numerical simulation 30 studies on the trapezoidal VG, so that the results from this study can be used to validate the results in the present research. However, for the near wall region treatment, the previous RSM study 30 used two‐layer model instead of standard wall treatment. The standard and two‐layer near wall treatment methods were compared here, and it was found that the results using the standard wall treatment are closer to the experimental data from PIV 7 .…”
Section: Grid Independency and Validationmentioning
confidence: 99%
See 3 more Smart Citations